(3JGL GdeaQb aj JMdjI YdeGA GdeTQbs - (3NGdO Hf YjSi Hf CMeO Hf EHQGgje Hf CHj NGdO GdHdhqj, CHh GdHbGA,J (B767 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aQV ML GdHjJ Ydi ef GSJWGY Edjg SHjdG s
(3BNQgG (B:s
(3Edi Cf NQLfG YTQ jhe GdKdGKGA bGd NGdO Hf CMeO GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs